The Pension Puzzle : Prerequisites and Policy Choices in Pension Design - Barr, N. (Washington, D.C. : International Monetary Fund, 2003)
Looks at the policy choices involved in creating pension schemes, particularly whether it is advisable to move away from government pay-as-you-go pensions toward private or publicly funded plans. Examines the reasons for the controversy surrounding pension design, and whether the second level of pension systems should be mandatory, private, funded, and defined-contribution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet